What is the appropriate treatment strategy for cryptogenic multifocal ulcerative stenosing enteritis? A single-center experience from China - Yan, Pengguang; Li, Kemin; Cao, Yang; Wu, Dong; Li, Ji; Qian, Jiaming; Zhou, Weixun; Li, Jingnan (Frontiers in Medicine, 2022)
Background: There are few reports on standard treatment and long-term prognosis in patients with cryptogenic multifocal ulcerative stenosing enteritis (CMUSE), particularly in patients in whom remission could not be induced by steroids. The aim of this study was to evaluate the treatment response and progression-free periods of patients with CMUSE and to identify the factors predictive of steroid resistance. Methods: This was a retrospective cohort study that included 25 patients with clinically confirmed CMUSE between 1984 and 2021 from the enteropathy clinic of a tertiary care center. For statistical analyses, chi-square test or Fisher's exact test were used for categorical variables. Survival curves were plotted using the Kaplan–Meier method. Results: The overall median progression-free period was 48 months (range, 1–108 months) after comprehensive therapy, and initial manifestation with severe bleeding rather than ileus was associated with the long-term efficacy. Patients with steroid resistance (N = 10, 55.6%) had poor prognosis, and non-responders had more favorable baseline clinical characteristics, with a higher percentage of female patients (60% vs. 12.5%), earlier disease onset (26.5 years vs. 39 years), rapid progression (42 vs. 108 months), severe anemia (80% vs. 50%), and hypoalbuminemia (50% vs. 0%), in accord with lymphangiectasia or angioectasia identified in pathology. Conclusions: Due to unknown etiology, there is no standard comprehensive treatment strategy for CMUSE, particularly in patients with steroid resistance. Further studies should differentiate CMUSE based on prostaglandin pathway function and assess the efficacy of integrated therapy, including targeted prostaglandin mediation.